Functorial Semiotics for Creativity in Music and Mathematics - Mazzola, Guerino; Dey, Sangeeta; Chen, Zilu.; Pang, Yan. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents a new semiotic theory based upon category theory and applying to a classification of creativity in music and mathematics. It is the first functorial approach to mathematical semiotics that can be applied to AI implementations for creativity by using topos theory and its applications to music theory. Of particular interest is the generalized Yoneda embedding in the bidual of the category of categories (Lawvere) - parametrizing semiotic units - enabling a Čech cohomology of manifolds of semiotic entities. It opens up a conceptual mathematics as initiated by Grothendieck and Galois and allows a precise description of musical and mathematical creativity, including a classification thereof in three types. This approach is new, as it connects topos theory, semiotics, creativity theory, and AI objectives for a missing link to HI (Human Intelligence). The reader can apply creativity research using our classification, cohomology theory, generalized Yoneda embedding, and Java implementation of the presented functorial display of semiotics, especially generalizing the Hjelmslev architecture. The intended audience are academic, industrial, and artistic researchers in creativity.
Part I Orientation -- Part II General Concepts -- Part III Semantic Math -- Part IV Applications -- Part V Conclusions -- References -- Index.
Keywords: Music-Mathematics.; Semiotics; Computational neuroscience; Art-Study and teaching; Artificial intelligence; Mathematics-Data processing; Mathematics in Music; Semiotics; Computational Neuroscience; Creativity and Arts Education; Artificial Intelligence; Computational Mathematics and Numerical Analysis